Migratory group of the ordinal relative words. Situation in system-structural space of a modern language (based on the Spanish and Portuguese) - N. V. Zenenko; M. A. Zenenko (Ибероамериканские тетради)
The article contains a functional-semantic analysis of the ordinal relative words primero and último, which constitute a migratory group. The semantic interpretation of these tokens to determine the location of the migration group in the system-language space structurally, antonymy define the framework and the functionality of these linguistic units.